2018
DOI: 10.1002/ece3.4521
|View full text |Cite
|
Sign up to set email alerts
|

Hidden cost of disease in a free‐ranging ungulate: brucellosis reduces mid‐winter pregnancy in elk

Abstract: Demonstrating disease impacts on the vital rates of free‐ranging mammalian hosts typically requires intensive, long‐term study. Evidence for chronic pathogens affecting reproduction but not survival is rare, but has the potential for wide‐ranging effects. Accurately quantifying disease‐associated reductions in fecundity is important for advancing theory, generating accurate predictive models, and achieving effective management. We investigated the impacts of brucellosis (Brucella abortus) on elk (Cervus canade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
2
4
1
Order By: Relevance
“…The reproductive performance of B. abortus seropositive individuals and their associated disease transmission risk is best understood across multiple years because infectiousness generally peaks the year after exposure and most elk control or clear the infection. Our finding that exposure to B. abortus decreased elk pregnancy rates by approximately 9.6% in prime-age elk and by 37.7% in old elk was similar to that of previous studies that found a 7–31% reduction in pregnancy rates of seropositive elk (Cotterill et al 2018b; Yang et al 2019). It is important to note the very small sample size for old elk ( n =4 seropositive, n =12 seronegative), which resulted in uncertainty around our predicted probabilities of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…The reproductive performance of B. abortus seropositive individuals and their associated disease transmission risk is best understood across multiple years because infectiousness generally peaks the year after exposure and most elk control or clear the infection. Our finding that exposure to B. abortus decreased elk pregnancy rates by approximately 9.6% in prime-age elk and by 37.7% in old elk was similar to that of previous studies that found a 7–31% reduction in pregnancy rates of seropositive elk (Cotterill et al 2018b; Yang et al 2019). It is important to note the very small sample size for old elk ( n =4 seropositive, n =12 seronegative), which resulted in uncertainty around our predicted probabilities of pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…While Cotterill, Cross, Middleton, et al (2018) had similar findings for elk exposed to brucellosis on winter feedgrounds, this pattern of long‐term reduced fertility as a result of previous exposure to brucellosis in unfed elk elsewhere in the GYE is a novel finding in this study. Additionally, Cotterill, Cross, Middleton, et al (2018) found a similar reduction in pregnancy probability due to brucellosis exposure (as much as 31 percentage‐points in 2‐year‐olds), but we report a stronger reproductive penalty for yearlings; a 21.4‐percentage‐point difference compared with 16 percentage‐points in Cotterill, Cross, Middleton, et al (2018). Samples for PSPB testing were taken between December and March, before most disease‐induced abortions typically occur (March–May, Cross et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Samples for PSPB testing were taken between December and March, before most disease-induced abortions typically occur (March-May, Cross et al, 2015). Thus, our results add to the growing body of evidence that elk exposed to (and likely infected by) B. abortus may suffer a reproductive penalty in subsequent years beyond the initial loss of pregnancy at first active infection (Cotterill, Cross, Middleton, et al, 2018). Yang et al (2018) suggest the mechanism for this penalty is not through nutrition, as little difference in body condition was found between seropositive and seronegative elk in Montana, despite an estimated 30% reduction in pregnancy rates for seropositive individuals.…”
Section: Reduced Fertility After Exposure To Brucellamentioning
confidence: 69%
“…However, with careful study design and interpretation, antibody prevalence can be an invaluable tool for understanding the disease dynamics, even in poorly studied systems such as wildlife populations. For example, in the GYA, although brucellosis does not have an obvious impact on population dynamics (National Academies of Sciences, Engineering, & Medicine, 2017), this infection can potentially reduce the growth rates of wild populations due to abortion events or even because of lower survival and pregnancy rates as shown for elk in the GYA (Cotterill et al, 2018; Cross et al, 2015) or for the African buffalo population of the Kruger National Park in South Africa (Gorsich, Ezenwa, Cross, Bengis, & Jolles, 2015). These changes may remain unnoticed without longitudinal and sustainable monitoring programmes.…”
Section: Discussionmentioning
confidence: 99%